Secondhand Brokerage: Evidence On The Importance Of Local Structure For Managers, Bankers, And Analysts - Burt, Ronald S. (Academy of Management Journal, 2007)
Analyzing network associations with performance in three study populations, I find that secondhand brokerage—moving information between people to whom one is only connected indirectly—often has little or no value. Brokerage benefits are dramatically concentrated in the immediate network around a person. Why that is so, and conditions under which it is more or less so, are examined. The research implication is that brokerage can be measured with designs in which data are limited to an immediate network. The theory implication is that the social capital of brokerage is a local phenomenon mirrored in the Austrian market metaphor's emphasis on tacit, local knowledge.